1993
DOI: 10.1111/j.1440-1681.1993.tb01714.x
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and Blood Pressure Regulation: Dose‐response Relationships for Angiotensin, Blood Pressure, Atrial Natriuretic Peptide and Aldosterone in Normal Subjects of Varying Ages

Abstract: 1. Infusion of increasing doses of angiotensin II (AII) in normal subjects sequentially increased blood pressure, aldosterone and atrial natriuretic peptide (ANP) levels. 2. The slope of ANP response to AII was positively correlated with basal ANP and with the slope of blood pressure response to AII (pressor slope) but not with age. 3. This is consistent with the response of ANP to AII being mediated partly by the rise in blood pressure, independent of ageing. 4. As expected in a selected normotensive populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Some investigators (4) have shown decreased vascular responsiveness with increasing age. Conversely, others (13) have shown an increased contractile effect to ANG II with increasing age. Still others (3) have reported no differences across age to the constrictor effect of ANG II.…”
Section: Discussionmentioning
confidence: 91%
“…Some investigators (4) have shown decreased vascular responsiveness with increasing age. Conversely, others (13) have shown an increased contractile effect to ANG II with increasing age. Still others (3) have reported no differences across age to the constrictor effect of ANG II.…”
Section: Discussionmentioning
confidence: 91%